2021
DOI: 10.5121/ijcseit.2021.11601
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Irrigation Monitoring and Control System

Abstract: In Uganda, as well as other developing countries, the increasing population stimulates the agricultural-related activities such as irrigation. Irrigation is basically done by humans and generally requires exhaustive physical efforts and involves exposure to errors during irrigation. Despite the advances in the irrigation and its wide spreading applications, irrigation remains majorly manual. Since irrigating is a difficult process especially when irrigating a big piece of land, it is necessary to simplify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Most common recommender systems make use of recommendation techniques such as content-based (CB), collaborative filtering (CF), and knowledge-based (KB) techniques, with each technique having their merits and demerits. This has led to the of the advent of many other advanced recommendation approaches such as context awareness-based recommender systems, computational intelligence-based recommendation systems, fuzzy recommender systems, social network-based recommender systems, and group recommender systems [3].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Most common recommender systems make use of recommendation techniques such as content-based (CB), collaborative filtering (CF), and knowledge-based (KB) techniques, with each technique having their merits and demerits. This has led to the of the advent of many other advanced recommendation approaches such as context awareness-based recommender systems, computational intelligence-based recommendation systems, fuzzy recommender systems, social network-based recommender systems, and group recommender systems [3].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, it has been observed that application study has become the main research focus of current recommender system research especially in this age characterised by big data such as: learning materials recommendations, films, music, tourism scenic spots, television programs, books, documents, websites, conferences, amongst others [4]. Clusters of eight main domains namely: e-commerce, e-learning, e-library, e-government, e-tourism, e-resource services and egroup activities are some of the application areas which these recommender systems involved in [3]. Our system is a hybrid system (e-education) which combines aspects linked to e-learning, etourism and e-group activities; e-library could also be part of it.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations